A Proposal of a Demand Shifting Function to Address the Demand-Capacity Imbalance of Capacity-Constrained Systems that Shift Demand by Discount Setting - BOYDON, CHRISTIAN; MARTINEZ, IRIS ANN; LORENZO, LOWELL (Philippine Engineering Journal, 2018)
Abstract – This paper addresses the problem of low profit of service establishments because of the imbalance between capacity and demand. The hypothesis of this paper is that profit can be maximized by shifting demand from high demand periods to low demand periods. The proposal of this research is to shift the demand through discount setting that is structured and optimized, which is the demand shifting function to be applied to maximize profit. This paper states general framework and the specific method to arrive at the recommended demand shifting function. Furthermore, it is applied to a real test case of a spa service facility. Results show that for the test case, profit is increased and the variability of demand among time periods is decreased. Keywords—demand-capacity imbalance, demand shifting function, service facility